AVALIAÇÃO DE POLÍTICAS PÚBLICAS: uma análise do programa de volta para casa - Andréia Cristina Barreto (Universidade Federal do Maranhão, 2013)
Developed around the theme of politics evaluation of the children and adolescent, the present article has as an objective to introduce the best results found in master degrees research around the theme of partnerships between Government and Non-governmental Organizations (ONGS) in the execution of the program "De Volta Para Casa" (Back Home). For the analysis of the mentioned issue, it was made a qualitative research, with semi-structural interviews, and a strong documental analysis of the 2008 to 2010 management reports. As the research shows the difficulties in the management, specially in rating and monitoring impact directly on the quality of the actions and in the achieved results. The data shows that the activities of evaluation have significative importance at the problems of management of the politics and social development programs. Beyond that they show the complexity of the subject of evaluation in the social field, particularly in its technical character / instrumental in practice